2001
DOI: 10.1046/j.1523-1747.2001.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-Dependent Apoptosis of Normal Dermal Fibroblasts

Abstract: The mechanisms underlying the contraction-dependent apoptosis of primary fibroblasts are of prime importance in understanding anchorage-dependent survival/apoptosis of dermal fibroblasts. As integrins are essential extracellular matrix receptors in fibroblasts, their role in anchorage-dependent apoptosis/survival of fibroblasts was analyzed. Primary human fibroblasts displayed a marked reduction of apoptosis in mechanically relaxed collagen matrices in the presence of adhesion-blocking antibodies against alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 35 publications
3
47
0
1
Order By: Relevance
“…Antibodies to a2b1 integrins prevent the contraction and reduce apoptosis. [97][98][99] Integrin a11 mRNA and protein are up-regulated in attached collagen gel and down-regulated in fibroblasts grown in floating gel. 100 Rat liver MFB utilize a1b1 integrin for collagen matrix contraction as a2 subunit is not expressed in HSC, their precursors in vivo.…”
Section: Floating Matrixmentioning
confidence: 99%
“…Antibodies to a2b1 integrins prevent the contraction and reduce apoptosis. [97][98][99] Integrin a11 mRNA and protein are up-regulated in attached collagen gel and down-regulated in fibroblasts grown in floating gel. 100 Rat liver MFB utilize a1b1 integrin for collagen matrix contraction as a2 subunit is not expressed in HSC, their precursors in vivo.…”
Section: Floating Matrixmentioning
confidence: 99%
“…In fact, studies carried out with various types of cultured cells have confirmed that changes in the balance of mechanical forces between cells and the ECM control all of the key cell behaviors that are responsible for tissue development. For example, cells make entirely different fate decisions, such as whether to grow, differentiate or die (i.e., undergo programmed cell death or "apoptosis"), depending on the adhesivity or mechanical compliance of their ECM substrate and thus, the degree to which they physically extend (Folkman and Moscona, 1978, Ben-Ze'ev et al, 1980, Glowacki et al, 1983, Li et al, 1987, Ben-Ze'ev et al, 1988, Ingber and Folkman, 1989, Opas, 1989, Ingber, 1990, Mooney et al, 1992, Singhvi et al, 1994, Dike et al, 1999, Niland et al, 2001. This can be accomplished by varying the density of immobilized ECM molecules on otherwise non-adhesive dishes; changing the flexibility of ECM gels; or creating planar ECM islands with defined size and shape on the micrometer scale using microfabrication techniques (Fig.…”
Section: Shape-dependent Control Of Cell Fate Switchingmentioning
confidence: 99%
“…For example, it has been found that increases in cell contractility and ECM stiffness promote cell proliferation 1,2 and assembly of focal adhesions, 3,4 whereas reduction in cell contractility and ECM stiffness induces cytoskeleton depolymerization 3 and apoptosis. 5,6 Several technical developments have enabled these recent insights into the role of mechanics in biology. These include the advent of two-dimensional (2D) substrates for cell culture that spans a range of physiologic stiffnesses 3,7 that can be used to apply force to cells, and whose deformations can be used to report cellular forces.…”
Section: Introductionmentioning
confidence: 99%